Islamic business ethics and practices of Islamic banks: perceptions of Islamic bank employees in Gulf cooperation countries and Malaysia - Musa, Muhammad Adli; Abd Sukor, Mohd Edil; Ismail, Mohd Nazari; Elias, Muhd Ramadhan Fitri (Emerald Publishing, 2020)
Purpose – The purpose of this paper is to empirically examine the perception of Islamic bank employees in Malaysia and selected Gulf Cooperation Council (GCC) countries, namely, Bahrain, Oman and the UAE, on various issues related to Islamic business ethics and the practices of the Islamic banks at which they work. Design/methodology/approach – The required data to determine Islamic bank employees’ ethical perceptions is sourced from 144 completed survey questionnaires and interviews with 12 Islamic bank senior executives. Islamic model of normative business ethics is used to measure the relationship between attitudes and behaviours of employees and the ethical practices of Islamic banks. Findings – Results show that the Islamic bank personnel working in Malaysia and the GCC perceived that their banks conform to Islamic ethical norms in business. These banks were seen to be concerned with their impact on society, and ethics prevailed over profit-maximisation. The findings also suggest that despite being less regulated compared to Malaysia, Islamic bank personnel in GCC had a better impression of the ethical standard practised in their institutions compared to the feedback given by their Malaysian counterparts. Additionally, this research also proves that, in general, there is a positive correlation between attitudes and behaviours of employees and the ethical practices of Islamic banks. Research limitations/implications – The main limitation of the study is that the respondents were not selected randomly but rather through a convenient sampling of personal contacts. Despite the inherent limitation of the sampling method because of the constraints of time and resources, the large number of respondents from 12 different banks are representative of the Islamic bank employees in Malaysia and the GCC. Practical implications – The findings may serve as a useful input for Islamic financial institutions in improving their practices to conform with Islamic ethical norms. Originality/value – The topic of Islamic business ethics and the practices of Islamic banks have not been fully understood by its stakeholders. This paper aims to give insights on how far Islamic bank business practices in Muslim majority societies fit with the prescribed business framework in Islam and its contributing value for both the organization and employees.